2020
DOI: 10.1089/phage.2020.0014
|View full text |Cite
|
Sign up to set email alerts
|

Bacteriophages Could Be a Potential Game Changer in the Trajectory of Coronavirus Disease (COVID-19)

Abstract: The pandemic of the coronavirus disease (Covid-19) has caused the death of at least 270,000 people as of the 8th of May 2020. This work stresses the potential role of bacteriophages to decrease the mortality rate of patients infected by the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) virus. The indirect cause of mortality in Covid-19 is miscommunication between the innate and adaptive immune systems, resulting in a failure to produce effective antibodies against the virus on time. Although fur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 52 publications
(67 reference statements)
0
28
0
Order By: Relevance
“…A recent study showed that SARS-CoV-2 behaves like a bacteriophage, meaning a virus that infects bacteria [ 93 ]. Genetic sequencing of microflora from six severely infected COVID-19 patients in the same family showed the presence of significant amounts of Prevotella in the feces [ 94 ].…”
Section: Effectiveness In Promoting Health: Mechanism Of Action Ofmentioning
confidence: 99%
“…A recent study showed that SARS-CoV-2 behaves like a bacteriophage, meaning a virus that infects bacteria [ 93 ]. Genetic sequencing of microflora from six severely infected COVID-19 patients in the same family showed the presence of significant amounts of Prevotella in the feces [ 94 ].…”
Section: Effectiveness In Promoting Health: Mechanism Of Action Ofmentioning
confidence: 99%
“…Further, excessive use of drugs can severely disrupt the microorganism communities in human bodies, causing massive elimination of beneficial microbes and aggressive selection of drug-resistant species (Croswell et al 2009;Lawley et al 2009;SanMiguel et al 2017). Infections by drug-resistant pathogens lead to higher morbidity and mortality in patients, and impose additional burden and costs on our society (Wojewodzic 2020). In the United States alone, at least 2.8 million people are infected with antibiotic-resistant bacteria each year, and more than 35,000 people eventually die from these infections (CDC 2019).…”
Section: Synthetic Drugs and Microbial Resistancementioning
confidence: 99%
“…Systems biologist Marcin Wojewodzic recently commented that phages could be used to help COVID-19 patients by suppressing bacterial co-infections and producing antibodies (Wojewodzic 2020). Indeed, some phages are known to prey on bacterial pathogens that can cause human respiratory failure.…”
Section: Phages As Predators For Bacterial Pathogensmentioning
confidence: 99%
“…Phage therapy will help control diseases involving antibiotic resistance. This is an insight into use of bacteriophages to control COVID-19 in a post-treatment-control era 44 . Research shows that other microorganisms enhance the activities of T cells by increasing their ability to respond to pathogenic microorganisms 45 .…”
Section: Benefits Of the Microbiotamentioning
confidence: 99%